ORGANIZATION OF PEDAGOGICAL EXPERIMENT ON IMPLEMENTATION OF METHODOLOGICAL SYSTEM OF FORMATION OF SELF-EDUCATIONAL COMPETENCE OF COMPETENCE - Gaida, Vasil (Physical and Mathematical Education, 2021)
Problem formulation. The article highlights the results of a pedagogical experiment on the implementation of the developed methodological system for the formation of self-educational competence of primary school students in the study of physics on the basis of sustainable development. In compliance with the principles of a systematic approach to the analysis and organization of the educational process of forming self-educational competence of primary school students in the educational process in physics, full compliance with pedagogical conditions of its implementation and providing a set of effective forms, methods, tools and technologies in the educational process, envisage the formation of a high level of self-educational competence of students of general secondary education institution. Materials and methods. During the implementation of the pedagogical experiment we used theoretical (analysis of scientific and methodological literature on the formation of self-educational competence of students), empirical (observation, questionnaires, testing), as well as statistical methods of processing research results (Pearson and Student’s test). A pedagogical experiment (ascertaining, searching, forming and final stages) was conducted, which involved 1227 students from 24 educational institutions of Ternopil (18), Volyn (3) and Kirovohrad (3) regions. Results. The results of the pedagogical experiment confirmed the statistical significance of the influence of the proposed methodological system on the qualitative indicators of self-educational skills and positive changes in the assimilation of teaching material in physics by students. Conclusions. The introduction of the developed methodological system contributes to: increasing students ’motivation for self-education, interest in studying physics, developing critical thinking, improving students’ ability to use cloud services to perform personal and socially significant tasks and educational projects, developing skills to use application software in physics, independence skills, group work, educational communication, etc.